Effects of serotonin transporter gene polymorphism on mood during the period before the competition in Japanese ballet dancers. Issue 6 (2016) - Yatabe, Kanaka; Kumai, Toshio; Fujiya, Hiroto; Yui, Naoko; Kasuya, Satomi; Murofushi, Yuka; Tateishi, Keisuke; Terawaki, Fumiko; Kobayashi, Hajime; Uchino, Aya; Kudo, Takaaki; Ohno, Mahiro; et al.
No abstract available